Bien jurídico protegido en los delitos contra el ambiente y la naturaleza (Tema Central) - Arias Benavides, Alejandra Nathaly (2024)
This article analyzes the influence of the recognition of the Rights of Nature in the 2008 Constitution, as a cause to the subsequence appearance of new protection settings in the structure and the criminal dogma of the Ecuadorian Criminal Law. It is done a brief comparison between the environmental protection model before the constitutional framework in force and its development considering the new paradigm; and it is studied in depth, which are the legal assets subjects to protect. To fulfill this, it was chosen the deductive methodology based on the bibliographic and normative analysis with the case study about the crimes Criminal Law used in this context. Thanks to this research, could verify the existence of a protection of the nature for its intrinsic value, however, this progress still lives together with the constant environment assessment to the usefulness for humans. It was concluded that because of the protection of new legal assets related with the nature appeared new punishable behaviors whose objective is to prevent and discipline not only the involvement of the environment as an object but also to the infringement of environments and natural ecosystems as complex and independent systems in attention to the constitutional mandate.